Assessing the potential impact on poverty of rising cereals prices : the case of Mali - Joseph, George (Policy research working paper, 2008)
"Concerns have been raised about the impact of rising food prices worldwide on the poor. To assess the (short term) impact of rising food prices in any particular country it is necessary to look at both the impact on food producers (who benefit from an increase in prices) and food consumers (who loose out when the price increases), with a focus on poor producers and consumers. In Mali the impact of a change in the price of rice is not ambiguous because about half of the rice consumed in the country is imported, so that the negative impact for consumers is much larger than the positive impact for producers. By contrast, for millet and sorghum, as well as corn, the impact is more ambiguous since much of the consumption is locally produced. Using a recent and comprehensive household survey, this paper provides an assessment of the potential impact of higher food prices on the poor in Mali using both simple statistical analysis and non-parametric methods. The paper finds that rising food prices for rice, millet and sorghum, corn, as well as wheat and bread could together lead to a substantial increase in poverty, with the increase in the price of rice having by far the largest negative impact. "--World Bank web site